Global Research Trends in Fashion Merchandising: A Bibliometric Review of Scopus Publications - Asna, Nailin Nuriyya; Nurmasitah, Sita (Journal of Creativity Student, 2026)
Research on fashion merchandising has grown in recent decades, yet systematic mapping of this field remains limited compared to other fashion-related domains. This study examines global research trends, intellectual structure, and thematic evolution in fashion merchandising through a bibliometric review. Data were collected from the Scopus database using the keyword “fashion merchandising” in the TITLE-ABS-KEY fields, yielding 337 publications published between 2006 and 2026. Bibliometric analysis was conducted using VOSviewer to identify publication trends, leading countries and institutions, influential journals and authors, and dominant research themes. The findings reveal a strong geographical concentration of research output in developed countries, particularly the United States and China, while contributions from developing economies remain limited. Thematic analysis highlights growing attention to retail strategy, consumer behavior, entrepreneurship, sustainability, and fashion education, indicating opportunities for more context-specific future research.